Evaluation of survival strategies used by Gweru small to medium enterprises in the motor oil industry - Mafumbate, J.; Mafuka, A. (Midlands State University, 2016)
This study sought to evaluate the survival strategies used by small to medium (SMEs) in the motor industry in Gweru during Zimbabwe s multicurrency regime (2009-2011). The main objectives of the study were to expose the strategies which used by SMEs in order to increase sales volumes and gain customer confidence. The study also sought to asses the quality of service rendered to clients. In this study, a descriptive research design was used. A judgmental sampling technique was used to select 200 respondents for interviews from a target population of 600 individuals. The results obtained showed that the SMEs survived through negotiating credit terms with their suppliers in which they were allowed a two week credit facility. The results also proved that quality of service offered by the SMEs in the motor industry was poor; as a result the customers were not satisfied. The findings further indicated that, the majority of the SMEs in the motor industry are not making any effort to try and increase their market share. This is because the SMEs lacked the funds to embark on promotional activities. This resulted in the customers losing confidence with the SMEs operations. This has also resulted in a decline in the sales volumes and a decline in profits. The respondents argued that government policies were too rigid and difficult to achieve. For instance the high duty level charged when importing car oils increased the SMEs operational costs. The authors recommended that the SMEs have to pool together their resources when purchasing oils so as to cut on the transport costs. The SMEs also need to employ skilled and qualified staff. This would enable the SMEs to price their products competitively at the same note offering quality customer service. This will also enable the SMEs regain the customers confidence.